Asymmetric synthesis of (−)- and (+)-neodichroine/hydrachine A from (+)- and (−)-febrifugine. Issue 17 (25th April 2018) - Smullen, Shaun; Evans, Paul
Graphical abstract: Highlights: New organocatalysis-based method for the synthesis of optically active febrifugine (both enantiomers). First total synthesis of reported quinolizidine natural product. Clarification of the structure of the reported natural product. Abstract: A new asymmetric approach to both enantiomers of the quinazolinone-containing natural product febrifugine is reported. Utilising a proline-mediated aminooxylation-Horner-Wadsworth-Emmons sequence provides the key optically active 2, 3-disubstituted piperidine intermediate7 in high enantioselectivity but poor overall yield (7 steps, 3%, 98% ee). This intermediate has been used to prepare both naturally occurring (+)-febrifugine (1 ) and its (−)-enantiomer. In turn, each were then used to synthesise, for the first time, both enantiomers of the claimed natural product neodichroine/hydrachine A. Spectroscopic data for the synthetic compound matched the claimed structure. However, the specific rotation differed in both magnitude and sign from the isolation work.